2010
DOI: 10.17305/bjbms.2010.2718
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Benefits on Metabolic Syndrome with Diet and Physical Activity

Abstract: e research has included  patients aged between  to , of whom  were men and  women. e purpose of research was to determine impact of diet and physical activity in the treatment of metabolic syndrome during the six month period. Processing of results through descriptive and discriminative analysis have indicated that  month treatment with diet and physical activity have had an impact in the: waistline decrease by , cm or , among males, and , cm or , among females; body mass index (BMI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…A similar study also noticed that lifestyle intervention significantly reduced the prevalence of central obesity, hypertriglyceridemia and incidence of diabetes [21]. A six-month treatment with dietary modification and medium intensity walking exercises also strengthen the findings of the present study [22].…”
Section: Resultssupporting
confidence: 88%
“…A similar study also noticed that lifestyle intervention significantly reduced the prevalence of central obesity, hypertriglyceridemia and incidence of diabetes [21]. A six-month treatment with dietary modification and medium intensity walking exercises also strengthen the findings of the present study [22].…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, physical activity is critical in the prevention of MetS (Cho et al ., 2009), and in managing the component metabolic problems (Dragusha et al ., 2010; Harralson et al ., 2010). It has even been suggested that interventions pairing patient education and physical activity can reverse MetS (Mujica et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that smoking initiation is most likely to occur in adolescence and young adulthood (Hill and Borland 1991), it may seem inefficient for primary care providers to continually discuss this issue with their patients, assuming that they have previously indicated they do not smoke. On the other hand, physical activity is critical in the prevention of MetS (Cho et al, 2009), and in managing the component metabolic problems (Dragusha et al, 2010;Harralson et al, 2010). It has even been suggested that interventions pairing patient education and physical activity can reverse MetS (Mujica et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…High-density lipoproteins decreased by 0.61% in Group A and decreased by 1.8% in Group B. Triglycerides in Group A decreased by 12.95 %, while Group B decreased by 3.77% (Rana et al, 2017). A study done to determine the effect of diet and physical activity in the treatment of metabolic syndrome during a 6 month period also shows signi icant decrease metabolic syndrome parameters with dietary modi ication and medium intensity walking of 4.5 km/hour (Dragusha et al, 2010).…”
Section: Association Between Socio-demographic Variables and Selectedmentioning
confidence: 97%